Intraoperative Shear Wave Elastography vs. Contrast-Enhanced Ultrasound for the Characterization and Differentiation of Focal Liver Lesions to Optimize Liver Tumor Surgery - da Silva, Natascha Platz Batista; Hornung, Matthias; Beyer, Lukas P.; Hackl, Christina; Brunner, Stefan; Schlitt, Hans Jürgen; Wiggermann, Philipp; Jung, Ernst Michael (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose Assessment of intraoperative quantitative shear wave elastography (SWE) and contrast-enhanced ultrasound (CEUS) for the characterization of focal liver lesions (FLLs) during liver surgery using postoperative histopathological results as the gold standard.Materials and Methods US data of 79 consecutive patients with 98 FLLs who underwent liver surgery between 08/2015 – 06/2017 were prospectively acquired and retrospectively analyzed. Multifrequency linear/T-shaped probes (6 – 9 MHz) were used to store cine loops of at least 5 s and images of B-mode, SWE and CEUS. The first CEUS loop was continuously documented over 1 min. in each case. Quantitative SWE analysis of FLLs was performed by placing 5 regions of interest to measure shear wave speed (m/s) and stiffness (kPa). CEUS was evaluated during the arterial, portal venous and late phase after i. v. bolus injections of 2.4 – 10 ml sulfur hexafluoride microbubbles. Postoperative histopathology after tumor resection or intraoperative biopsy was obtained to confirm findings of SWE and CEUS.Results Of 98 FLLs in 79 patients (mean age: 58 years sd ± 12y) 88 were malignant and 10 were benign ranging from 0.69 to 15.2 cm in size (mean: 2.8 cm, sd ± 2.25 cm). SWE characterized 73/88 FLLs correctly as malignant and 7/10 as benign using a cut-off value of 2.5 m/s/21.3 kPa (p < 0.0005). The sensitivity was 83 %, specificity 70 %, accuracy 82 %. CEUS could correctly identify 86/88 malignant and 8/10 benign FLLs. The sensitivity was 98 %, specificity 80 %, accuracy 96 %. SWE could correctly identify 2 malignant FLLs which CEUS falsely characterized as benign.Conclusion Intraoperative CEUS and SWE are excellent tools for the highly accurate visualization, characterization and malignancy assessment of hepatic tumors during liver surgery.
Keywords: intraoperative ultrasound; shear wave elastography; CEUS; liver tumor surgery